The Political University in Argentina in the 1990’s - Chiroleu, Adriana; Iazzetta, Osvaldo; Voras, Claudia; Diaz, Claudio (Education Policy Analysis Archives, 2001)
Although university autonomy was apparently protected during Carlos Menem's government (1989-1999), actually it was gradually undergoing substantial changes. "Intrusive" devices had been prepared by the executive power, thus causing the restriction of its objectives. This kind of state participation was less explicit than in the past, being now associated with the establishment of a system of "punishment and reward," in which financing is subordinated to "performance," evaluated according to the parameters of multilateral credit organizations . In this work, we analyse the way in which this conflict took place under Menem's government, contrasting the meanings given to the idea of autonomy by the government and by the public institution; attentin focuses on the case of the National University of Rosario.